Bicentennial man [videorecording (DVD)] - Columbus, Chris; Columbus, Chris; Williams, Robin, 1951-2014; Neill, Sam; Davidtz, Embeth, 1966-; Crewson, Wendy; Asimov, Isaac, 1920-1992; Asimov, Isaac, 1920-1992 (Touchstone Home Video ; Distributed by Buena Vista Home Entertainment, 2000)
A comedy about an android "household appliance" robot who just wants to be a regular guy.